Dari Sikap hingga Niat: Studi TPB atas Penggunaan Pengisi Daya Kendaraan Listrik di Rumah - Feby Rante Limbong; Harmanda Berima Putra (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study analyzes customers’ intentions to use home electric vehicle (EV) charging services at PT PLN (Persero) UP3 Serpong by applying the Theory of Planned Behavior (TPB) framework. The research focuses on the influence of subjective norms, perceived behavioral control, and attitudes on intention. Using a quantitative method and purposive sampling, data were collected from 160 large household customers through questionnaires and analyzed using PLS-SEM. The results show that perceived behavioral control has a positive effect on both attitudes and customer intentions, whereas subjective norms have no significant effect. Furthermore, attitudes have a positive effect on intention and mediate the influence of perceived behavioral control, but do not mediate the effect of subjective norms.